α-Mangostin prevents diabetic cardiomyopathy by inhibiting oxidative damage and lipotoxicity through the AKT–FOXO1–CD36 pathway - Bai, Xue; Zhang, Ziqian; Zhang, Miao; Xu, Jiaojiao; Dong, Keting; Du, Qian; Chen, Lei; Ma, Ping; Yang, Jianhong (Frontiers in Pharmacology, 2025)
IntroductionDiabetic cardiomyopathy (DCM), a cardiac complication of diabetes, is the main cause of the high prevalence of heart failure and associated mortality in diabetic patients. Oxidative stress and lipid metabolism disorder-induced myocardial cell damage are part of the pathogenesis of DCM. In this study, we investigated the effects of alpha-mangostin (A-MG), a natural antioxidant extracted from mangosteen peel, on in vitro and in vivo DCM models.MethodsH9C2 rat cardiomyocytes were treated with high glucose (HG) and palmitic acid (PA) for 24 h to establish an in vitro DCM cell model. Cell viability and cytotoxicity were evaluated after treatment with varying concentrations of A-MG (0.3, 1, 3, 9, or 27 μM) using Cell Counting Kit-8 (CCK8) and lactate dehydrogenase (LDH) assays. Flow cytometry assessment was used to detect apoptosis. Molecular mechanisms were investigated through transcriptome analysis, quantitative PCR (RT-qPCR), and Western blotting. Type 2 diabetic (T2D) mice, induced by feeding a high-fat diet (HFD) combined with low-dose streptozotocin (STZ), received either vehicle, low-dose A-MG (100 mg/kg/d), or high-dose A-MG (200 mg/kg/d) for 6 weeks. Cardiac function was assessed by echocardiography. H&E and Masson’s staining were used to evaluate cardiac tissue structure and fibrosis, and Western blotting was used to evaluate myocardial protein expression.ResultsIn HG/F-induced H9C2 cells, A-MG (1 and 3 μM) significantly increased cell viability (p < 0.01) and reduced LDH release (p < 0.05). A-MG (3 μM) attenuated lipid accumulation (p < 0.05), normalized mitochondrial membrane potential (p < 0.01), and inhibited reactive oxygen species (ROS) generation (p < 0.05), malondialdehyde (MDA) production (p < 0.01), and apoptosis (p < 0.05). A-MG also inhibited the nuclear translocation of Forkhead box class O1 (FOXO1) (p < 0.05); reduced the expression of CD36 (p < 0.05), PPARα (p < 0.01), and CPT1β (p < 0.05) proteins; enhanced superoxide dismutase (SOD) activity (p < 0.05); and upregulated nuclear factor erythroid 2-related factor 2 (Nrf2) (p < 0.01), HO-1 (p < 0.05), and SOD2 (p < 0.05) protein expression levels. Further investigation in HG/F-induced H9C2 cells indicated that A-MG inhibits the uptake of fatty acids (FAs) by regulating the AKT/FOXO1/CD36 signaling pathway, reduces excessive β-oxidation of FAs mediated by PPARα/CPT1β through the inhibition of FOXO1 nuclear translocation, and stimulates the AKT/Nrf2/HO-1 signaling pathway to increase the cellular antioxidant capacity. In diabetic mice, low-dose A-MG treatment increased anti-oxidative stress capacity, decreased myocardial lipid accumulation, reduced fibrosis and cardiomyocyte apoptosis, and improved left ventricular contractile function.ConclusionUsing both in vitro and in vivo DCM models, our study demonstrates that A-MG reduces lipid accumulation and excessive mitochondrial β-oxidation while enhancing antioxidant capacity. These results suggest that A-MG may be a novel therapeutic option for DCM.